2018
DOI: 10.1016/j.psychres.2018.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Prospective associations of physical fitness and cognitive performance among inpatients with Schizophrenia

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…For instance, cross‐sectional studies have demonstrated differential associations between physical fitness (e.g., muscular strength) and motor fitness (e.g., agility, flexibility, balance, and coordination) and cognitive functioning in older adults (Voelcker‐Rehage, Godde, & Staudinger, ). Further, recent studies have shown that cardiovascular fitness and body composition were associated with better cognitive performance (attention, speed of processing, working memory), but the association was not shown with measures of muscular strength (Chen, Hao, Ku, & Stubbs, ). In contrast, Narazaki et al () indicated that each of the five measured physical fitness parameters (upper extremity strength, lower extremity strength, extremity agility, locomotive coordination, and postural balance) were associated with performance on the Montreal Cognitive Assessment after controlling for confounding factors (age, sex, education, and body mass index), suggesting that different aspects of physical fitness may have similar or equivalent cognitive benefits.…”
Section: Introductionmentioning
confidence: 94%
“…For instance, cross‐sectional studies have demonstrated differential associations between physical fitness (e.g., muscular strength) and motor fitness (e.g., agility, flexibility, balance, and coordination) and cognitive functioning in older adults (Voelcker‐Rehage, Godde, & Staudinger, ). Further, recent studies have shown that cardiovascular fitness and body composition were associated with better cognitive performance (attention, speed of processing, working memory), but the association was not shown with measures of muscular strength (Chen, Hao, Ku, & Stubbs, ). In contrast, Narazaki et al () indicated that each of the five measured physical fitness parameters (upper extremity strength, lower extremity strength, extremity agility, locomotive coordination, and postural balance) were associated with performance on the Montreal Cognitive Assessment after controlling for confounding factors (age, sex, education, and body mass index), suggesting that different aspects of physical fitness may have similar or equivalent cognitive benefits.…”
Section: Introductionmentioning
confidence: 94%
“…Negative effects of schizophrenia on daily functioning and subjective well-being have been well Archives of Psychiatry and Psychotherapy, 2019; 1: [28][29][30][31][32][33][34][35] documented [4]. Among some of its other characteristics remain reduced physical activity, poor physical health, and limited daily activity [5].…”
Section: Mortality and Comorbidity In Schizophreniamentioning
confidence: 99%
“…To magnify the pro-cognitive effects, recent designs have shifted toward combining exercise interventions with cognitive rehabilitation [34]. However, some data suggest that better physical fitness may not necessarily ensure improved cognitive performance in people with established schizophrenia and baseline evidence of cognitive dysfunction [35]. A systematic review [36] investigating the pro-cognitive effects of exercise in schizophrenia patients suggested their increased brain volume, though with no specific mention of any particular brain region, while data on physical activity's effects on BDNF levels was somewhat inconclusive.…”
Section: Effects Of Physical Activity Interventions In Schizophrenia mentioning
confidence: 99%
See 1 more Smart Citation
“…Aerobic exercise can fight metabolic syndrome in obese people and is beneficial to cognitive improvement in people with mental disorders ( 10 , 11 ). In recent years, accumulating evidence has suggested that physical exercise and physical activity can help to prevent and treat schizophrenia or rehabilitate patients with the disorder ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%